Reaktor Pengolah dengan Sistem Biofilter untuk Menurunkan BOD dan TSS Limbah Cair Industri Susu Agro Prima di Turi, Sleman, Yogyakarta - Muhammad Azis Syarifudin; Narto Narto; Herman Santjoko (Poltekkes Kemenkes Yogyakarta, 2020)
Etawa goat milk industry located in Kemirikebo, Girikerto, Turi, Sleman, Yogyakarta do not have waste water treatment. Waste water from dairy industry contains abundant organic materials. Based on the preliminary survey the results of BOD levels were 518 mg l and the TSS levels were 234 mg/l. The dairy industry's waste water has direct impact on the environment and public health. An alternative to treat the waste waste is by using biofilter system wastewater treatment reactor with bioball media. The purpose of this research is to know the qualty improvement of the wastewater by using this reactor. The research type was an experiment with pre-test post-test with control design, and was conducted in February to April 2019. The data were analyses by employing independent sample t-test with ? = 0.05. The study results show that the mean de-crease for BOD levels in the control group was 6,79% and in the treatment group was 90,27%. In terms of TSS levels, the mean decrease in the control group was 8,98% and in the treatment group was 68,59%. It can be concluded that the wastewater treatment reactor affects the quality of wastewater of Agro Prima dairy industry.